Penggunaan Alat Kontrasepsi dalam Perspektif Ahkamul Fuqoha: Analisis Metodologi Ijtihad dan Fatwa LBM NU - Supardiyono, Shofwan; Hidayati, Tri Wahyu; Multazam, Umar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This article explores the Islamic legal perspective on the use of contraceptives, particularly through the lens of Ahkamul Fuqoha and the decisions of Nahdlatul Ulama’s Legal Advisory Council (LBM NU). Employing a qualitative method with a normative-theological approach, this study is based on comprehensive literature analysis. The findings indicate that LBM NU formulates legal rulings on contraception using a collective ijtihad (istinbath jama’i) methodology grounded in the objectives of Islamic law (maqashid al-shari’ah). Contraceptive use is considered permissible (mubah) if not permanent and aimed at protecting health, family welfare, and adhering to Islamic ethical guidelines. This reflects the adaptive nature of Islamic jurisprudence in addressing contemporary social challenges in Indonesian Muslim society.